Communication challenges faced by deaf patients in Zimbabwe’s health domain (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
This article explores the politics of inclusion and exclusion of the Deaf community in Zimbabwe's health sector, focusing on the marginalisation of Sign Language. It examines the use of Sign Language in major referral hospitals such as Parirenyatwa and Sally Mugabe, and the attitudes of nurses and doctors towards its use. The research aims to understand the lack of resources and programmes for the deaf community, as medical practitioners primarily use spoken language for communication. Data for the study were collected through questionnaires directed to the administration, doctors, nurses and Deaf patients at Parirenyatwa and Sally Mugabe Hospitals, and from two bus termini where the deaf are concentrated. Supplementary data were collected through focus group discussions and interviews with the Deaf. Data were presented and analysed using a thematic approach. The findings of the study are that there is no defined use and awareness of Sign Language in hospitals, and where there is awareness; the interventions have been weak, thereby failing to ameliorate communication challenges in healthcare settings.
Keywords: health communication; sign language; language rights; language policy